Power control scheme for device‐to‐device communication using uplink channel in 5G mm‐Wave network - Sarma, Subhra Sankha; Khuntia, Pratap; Hazra, Ranjay (Transactions on emerging telecommunications technologies, 2022)
Mm‐Wave communication ushers next‐gen communication to new heights guaranteeing higher speed and throughput. Enabling device‐to‐device (D2D) communication in next‐gen wireless communication is a Herculean task. This is due to introduction of pathloss attenuation by various environmental factors which deteriorates the signal. This article aims to minimize the effect of interference for quality reception of signals for D2D communication and increase system throughput. Thus, a power control scheme is proposed in underlay mode for uplink channel in mm‐Wave band. Here, D2D communication takes place through two modes namely, general mode and mm‐Wave mode. In presence of large number of proximity D2D users and increasing pathloss attenuation, it switches to mm‐Wave mode for communication. The formulated problem is converted to semiconvex form by expressing it into exponential form in Laplace domain. Our final objective is to maximize the energy efficiency (EE) of the proposed system under certain constraints. To reduce complexity of the problem, feasible regions of transmission power is introduced, that is, least and upper bounds which will ensure that power is maintained within a limit guaranteeing better throughput for D2D users. Enhanced EE and outage probability values also depict better performance of proposed system. Finally, fairness index (FI) shows that the proposed scheme yields better performance for the D2D users to communicate in the mm‐Wave band. A detailed comparison of FI for the proposed scheme is also done with other existing methods to prove the adequate performance of the proposed method. Simulation results also prove the efficacy of the proposed scheme. This article aims to minimize the effect of interference for quality reception of signals for D2D communication and increase system throughput through a power control scheme in underlay mode for uplink channel in mm‐Wave band.